CARDIOVASCULAR DISEASES AND METABOLIC-ASSOCIATED FATTY LIVER DISEASE: A MODERN PERSPECTIVE ON THE PROBLEM (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article examines the interrelationship between cardiovascular disease (CVD) and metabolic-associated fatty liver disease (MAFLD), highlighting how MAFLD is an independent cardiometabolic risk factor and emphasizing early detection and integrated management to reduce cardiovascular risk. MAFLD prevalence is high globally and rising, especially among high-risk groups; obesity, type 2 diabetes, dyslipidemia, and hypertension commonly cluster with MAFLD. There is evidence linking MAFLD to subclinical and clinical CVD, with insulin resistance and metabolic syndrome playing important roles; MAFLD may drive adverse myocardial remodeling and diastolic dysfunction. Development of improved non-invasive biomarkers for inflammation and fibrosis is a priority to better predict disease progression and guide treatment.